Resistant and refractory migraine – two different entities with different comorbidities? Results from the REFINE study - C. Rosignoli; R. Ornello; V. Caponnetto; A. Onofri; S. Avaltroni; M. Braschinsky; O. Šved; R. Gil-Gouveia; C. Lampl; J. Paungarttner; P Martelletti; W. D. Wells-Gatnik; et al. (The Journal of Headache and Pain)
Abstract Background Resistant and refractory migraine are commonly encountered in specialized headache centers. Several comorbidities, mostly psychiatric conditions, have been linked to migraine worsening; however, there is little knowledge of the comorbidity profile of individuals with resistant and refractory migraine. Methods REFINE is a prospective observational multicenter international study involving individuals with migraine from 15 headache centers. Participants were categorized into three groups based on the European Headache Federation criteria: non-resistant and non-refractory (NRNRM), resistant (ResM), and refractory (RefM). We explored the prevalence of 20 comorbidities at baseline in the three groups. Results Of the 689 included patients (82.8% women), 262 (38.0%) had ResM, 73 (10.4%) had RefM and 354 (51.4%) NRNRM. A higher prevalence of psychiatric comorbidities, trigger points, temporomandibular joint disorders, thyroiditis, and cerebrovascular diseases was observed in the RefM group, followed by ResM and NRNRM. Multiple comorbidities were more common in the RefM group, followed by the ResM group and by the NRNRM group (41.6% vs. 24.5% vs. 14.1% respectively; p < 0.001). At the sensitivity analysis, exploring participants with chronic migraine, significant differences among the NRNRM, ResM, and RefM groups were found in the prevalence of anxiety (p < 0.001), asthma and rhinitis (p = 0.013), bipolar and other psychiatric disorders (p = 0.049), cerebrovascular diseases (p < 0.001), depression (p < 0.001), obesity (p = 0.002), thyroiditis (p < 0.001), and trigger points (p = 0.008). Conclusion REFINE data indicate that individuals with ResM and RefM have a higher burden of comorbidities than those with NRNRM. It can be postulated that those comorbidities may have an impact on the progression of migraine from a form that is easy to treat to a form that is resistant or refractory to treatments. Longitudinal studies are needed to understand the direction of the association between ResM or RefM and those comorbidities and if proper treatment of comorbidities might help overcome treatment resistance or refractoriness.